Escherichia Coli Infections, and Antimicrobial Resistance in Poultry Flocks, in North Central Nigeria - Akanbi, Olatunde Babatunde; Olorunshola, Isaac Dayo; Osilojo, Peter; Ademola, Eunice; Agada, Godwin; Aiyedun, Julius; Odita, Christiana Ibironke; Ola-Fadunsin, Shola David (Universitas Airlangga, 2022)
To investigate Eschericiacoli infections in poultry flocks, 291 tissue samples from 237 necropsied carcasses submitted from ninety-nine (99) poultry flocks in north central Nigeria were analysed. These flocks comprised layer chicken, broiler, pullet, cockerel, turkey, quail, guinea fowl and ducks. Tissue samples were pre-enriched in 10 mL buffered peptone water media and aliquots were inoculated into selective enrichment broth, sub-cultured onEosin Methylene Blue (EMB) agar and MacConkey agar (MCA) and colonies of E. coli was examined based on cultural morphological characteristics. Layer poultry and laying quails exhibited reproductive lesions which correlates with history of disruption and reduction in egg production. Antibiotics resistance rate was significant (p <0.01) with macrolide and penicillin classes been the most resistant antibiotics in layers and broiler, while quinolones and aminoglycoside were most significantly susceptible (p <0.01). Multidrug resistance (MDR) was found in 56% of the E. coli isolates, with high prevalence in younger birds.